The use a virtual interactive system to enhance gynecologic oncology multi-disciplinary care in Zambia. (September 2021) - Pattee, Katerina; Msadabwe, Susan; Pfaendler, Krista; Mupeta, Songwe; Lishimpi, Emily; Zambezi, Wila; Sinkala, Charity; Chipampe, Mercy; Nteeni, Mutinta; Jere, Sydney; Kalima-Munalula, Mukatimui; Kamfwa, Paul; et al.
Highlights: MDT approach in cancer care improves outcomes and the patient experience. Digital technology can bridge gaps in healthcare in low resource environments. Integration of digital technology in LMIC cancer care is feasible. Abstract: Background: Gynecologic malignancies represent a significant proportion of the increasing cancer burden in Zambia. The care and outcomes of cancer patients improves in a multidisciplinary team but insufficient coordination in weak health systems is a barrier to this model of care. The World Health Organization (WHO) identifies digital health interventions as tools to bridge the gap between challenges and health systems' goals in low resource environments. A low-cost innovative virtual interaction system (VIS) was integrated into the gynecologic oncology multidisciplinary tumor board to enhance patient navigation and management. Methods: Paper-based forms used by each specialist group participating in the tumor board were collected and placed on a digital platform. Tumor board members were interviewed to assess their acceptability of the new digital modules and ensure correct nomenclature was being used for data entry. This was followed by an orientation and launch of VIS. Results: For a 12-week period following the launch, 197 gynecologic oncology patients were registered at the Zambian national cancer center (Cancer Diseases Hospital), of which 130 were entered in the VIS, and of those less than half had management decisions recorded. The median time from first visit to simulation for radiotherapy was 52 days; from simulation to start of treatment 102.5 days. Eighteen (14 %) of the 130 patients entered into the VIS were recorded as lost to follow up. Conclusion: The introduction and implementation of a digital intervention for navigation and management of gynecologic patients in a low resource environment proved both feasible and acceptable. It provides an instant easily accessible platform for important information on time intervals and delays in the patient pathway. End user orientation and support is an integral part to its successful integration and consistent management of the data is required to maximize its impact on efficiency, effectiveness and patient care.